2008
DOI: 10.1017/s0007485308006433
|View full text |Cite
|
Sign up to set email alerts
|

Factors limiting the species richness of bees in Saharan Africa

Abstract: There is a severe shortage of knowledge of bee biogeography. Some former studies have highlighted a link between bee diversity and xeric ecosystems, but we know practically nothing of the macro-ecological factors driving bee diversity. The present study aims to analyse the main macro-ecological factors driving bee species-richness in the Saharan region. Our dataset includes 25,000+ records for localities in Africa, between 37 degrees and 10 degrees N. Maps and GIS were used to get a first overview of the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
3
14
0
Order By: Relevance
“…Variety of food sources represented by richness of vascular plants and centres of plant diversity was significant at all scales and appeared to be the strongest predictor of bee species richness as already presumed by Patiny et al (2009a). For example, the global Colletinae species richness hot-spot in the GCFR coincides with one of the most prominent centres of plant diversity and endemism (Kuhlmann 2009).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Variety of food sources represented by richness of vascular plants and centres of plant diversity was significant at all scales and appeared to be the strongest predictor of bee species richness as already presumed by Patiny et al (2009a). For example, the global Colletinae species richness hot-spot in the GCFR coincides with one of the most prominent centres of plant diversity and endemism (Kuhlmann 2009).…”
Section: Discussionmentioning
confidence: 65%
“…northern Atacama, Sahara) or are found in the moist tropics, both unfavourable for bees. Areas too xeric for optimal bee diversity are extensive in the Afrotropical and Palaearctic Realms where the relationship between growing degree days and species richness was significantly negative and where bee diversity appears to be driven by optimal (rather than maximal) ecosystem energy (Patiny et al 2009a). Irradiance of the warmest quarter, on the other hand, was positively related to bee richness on the global scale, and in the Neotropical, Nearctic and Palaearctic Realms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on original datasets for duly chosen model taxa, patterns in the distribution of species richness in the southern WestPalaearctic have been described in a couple of papers Patiny et al, 2009). These latter studies have shown that (i) Maghreb and the Nile delta have remarkably high species richness; (ii); Morocco constitutes remarkable hotspot for bee species richness; (iii) The area between western Egypt and southeastern Tunisia is, by contrast, characterized by a very low level of species richness.…”
Section: Eastern and Southern West-palaearcticmentioning
confidence: 99%
“…These latter studies have shown that (i) Maghreb and the Nile delta have remarkably high species richness; (ii); Morocco constitutes remarkable hotspot for bee species richness; (iii) The area between western Egypt and southeastern Tunisia is, by contrast, characterized by a very low level of species richness. Based on a multivariate analysis of the macroecological parameters of the species richness distribution in the southern West-Palaearctic, Patiny et al (2009) concluded that the patterns of species richness in Saharan Africa (northern and southern) are ruled by the water/energy balance within ecosystems, which impacts on bees through their feeding resources (i.e. flowering plants).…”
Section: Eastern and Southern West-palaearcticmentioning
confidence: 99%